The politics of hate: how the Christian Right darkened America's political soul - Wilson, Angelia R. (Religious engagement in democratic politics, 2025)
"Explores how the Christian Right in the United States has learned to overcome both a lack of political professionalism within national, independent, theologically-based activist groups and theological divides that threatened political collaboration"--